THE SEMIOTIC NATURE OF INTONATION - Khromov Sergey Sergeevich (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2014)
The article is devoted to the main approaches to intonation analysis – the semiotic nature of intonation is discussed. The author proves the fact that intonation is a bilateral phenomenon having a content plan and an expression plan, and reveals the features of intonation as a sign: its complex character, simultaneous expression of different functions in a discourse, hierarchical character of meanings, high level of abstraction. The features of intonational sign are described in the following aspects: syntagmatic, paradigmatic and pragmatic. The author states that intonation represents an autonomous subsystem of the language manifesting both general semiotic patterns and specific rules of functioning.